Powering the Static Driver Verifier using Corral - Lal, Akash; Qadeer, Shaz (Foundations of Software Engineering (FSE), 2014)
The application of software-verification technology towards building realistic bug-finding tools requires working through several precision-scalability tradeoffs. For instance, a critical aspect while dealing with C programs is to formally define the treatment of pointers and the heap (usually termed as the “memory model”). A machine-level modeling is often intractable, whereas one that leverages high-level information (such as types) can be inaccurate. Another tradeoff is modeling integer arithmetic. Ideally, all arithmetic should be performed over bitvector representations (like what happens in the hardware), whereas the current practice in most tools is to use mathematical integers for scalability. A third tradeoff, in the context of bounded program exploration, is to choose a bound that ensures enough coverage without overwhelming the analysis. This paper works through these three tradeoffs when we applied Corral, an SMT-based verifier, inside Microsoft's Static Driver Verifier (SDV). Our decisions were guided by experimentation on a large set of drivers; the total verification time exceeded well over a month. We justify that each of our decisions were crucial in getting value out of Corral and led to Corral being accepted as the engine that powers SDV in the Windows 8.1 release, replacing the SLAM engine that had been used inside SDV for the past decade. This paper won the Distinguished Paper Award at FSE 2014.
ACM SIGSOFT Distinguished Paper